Effect of the barrier thickness on the performance of multiple-quantum-well InGaN photovoltaic cells. (25th June 2015) - Redaelli, Luca; Mukhtarova, Anna; Ajay, Akhil; Núñez-Cascajero, Arántzazu; Valdueza-Felip, Sirona; Bleuse, Joël; Durand, Christophe; Eymery, Joël; Monroy, Eva
Abstract: The impact of the barrier thickness on the performance of In0.17 Ga0.83 N multiple-quantum-well (MQW) solar cells is studied. When the barrier thickness is reduced from 9.0 to 3.7 nm, the effect of the internal polarization fields on the MQW band structure results in a blueshift of the cell photoresponse. At the same time, the overlap of the fundamental electron and hole wave-functions in the quantum wells increases and the carrier extraction by field-assisted tunneling is enhanced, impacting the external quantum efficiency and fill-factor of the cells. The experimental results show that the performance of the thinner-barrier cells studied in this work is superior, or at least comparable to the performance of their thicker-barrier counterparts, in spite of the smaller total thickness of their absorbing region. This is due to their higher external quantum efficiency (37% at 370 nm) and improved fill-factor (62%), which result in a conversion efficiency of η = 0.82%.